2020
DOI: 10.1002/1878-0261.12645
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming acquired resistance of EGFR‐mutant NSCLC cells to the third generation EGFR inhibitor, osimertinib, with the natural product honokiol

Abstract: The development of acquired resistance to osimertinib (Osim) (AZD9291 or TAGRISSOTM), an FDA‐approved third‐generation epidermal growth factor receptor (EGFR) inhibitor for the treatment of EGFR‐mutant nonsmall cell lung cancer (NSCLC), limits the long‐term benefits for patients. Thus, effective treatment options are urgently needed. To this end, we explored whether honokiol (HNK), a natural product with potential antitumor activity, may be used to overcome Osim resistance. The combination of HNK and Osim syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…As regards lung cancer, significant progress has been made in the research of natural product-based nanomedicines [ 163 , 164 ] and combination drug therapies [ 165 , 166 ], which can provide some reference for the related drug discovery and development for COVID-19. In this section, we mainly focused on the nanodrug strategy (containing natural products and FDA-approved drugs) to reveal its unique advantage in the research and development of anti-lung cancer drugs.…”
Section: Natural Products In Combination With the Fda-approved Anti-lung Cancer Drugsmentioning
confidence: 99%
“…As regards lung cancer, significant progress has been made in the research of natural product-based nanomedicines [ 163 , 164 ] and combination drug therapies [ 165 , 166 ], which can provide some reference for the related drug discovery and development for COVID-19. In this section, we mainly focused on the nanodrug strategy (containing natural products and FDA-approved drugs) to reveal its unique advantage in the research and development of anti-lung cancer drugs.…”
Section: Natural Products In Combination With the Fda-approved Anti-lung Cancer Drugsmentioning
confidence: 99%
“…Cisplatin is one of the most commonly used platinum-based chemotherapeutic agents and has shown efficacy in the treatment of various types of cancer, including breast cancer [ 76 ], lung cancer [ 77 ], and HNC [ 78 , 79 ]. The mode of utilization of cisplatin has undergone changes a number of times since it was first discovered in 1978 [ 80 , 81 ].…”
Section: Platinum-based Agentsmentioning
confidence: 99%
“…Our search criteria included the following terms: “osimertinib,” “resistance,” “lung cancer,” and “cell line” or “cell lines.” We also manually scanned the reference lists of selected articles for additional eligible publications. We finally identified 29 relevant papers [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. We excluded 2 of these papers [ 47 , 49 ], as they used osimertinib-resistant cell lines that had been established in other studies included in our survey.…”
Section: Cell Line Models Used To Analyze Resistance Mechanisms Tomentioning
confidence: 99%
“…The authors showed that MEK inhibitors (GSK1120212 or PD-0325901) combined with osimertinib reduced MCL-1 expression and could overcome the resistance [ 34 ]. The same group reported in a later study that honokiol (a natural product isolated from the bark, seed cones, and leaves of trees belonging to the genus Magnolia ) plus osimertinib enhanced MCL-1 reduction by suppressing ERK-dependent MCL-1 phosphorylation [ 47 ], and that the histone deacetylase inhibitor (LBH589) enhanced the effects of osimertinib in the resistant cells by decreasing levels of p-ERK and increasing BIM levels [ 49 ]. Another group reported that in experiments using PC9 and H1975 cells, BIM downregulation was the mechanism of AR to osimertinib.…”
Section: Cell Line Models Used To Analyze Resistance Mechanisms Tomentioning
confidence: 99%
See 1 more Smart Citation